Analysis of the reality of public debt in the Iraqi economy for the period (2004-2020( - Salman Al-Waeli, Ahmed; Kazem Al-Atabi, Samer (Humanities Journal of University of Zakho, 2023)
The research focuses on nalysing the development of public debt in Iraq for the period (2004-2020), considering that public debt is one of the sources of financing the state’s general budget deficit, which in turn is reflected in the structure of economic growth in Iraq. Public revenues, which led to a deficit in the public budget, as it was covered by public debt, and this reflected negatively on the local economy. One of the most important results of the research is the increase in the fiscal deficit in public budgets due to expansionary financial policies that led to an increase in internal and external public debt, as increases in public spending exceeded increases in public revenues because Iraq is mired in more than one political and military crisis, in addition to an increase in public spending as a result of the shock The dual nature of Iraq in the 2014-2016 period, which led to an increase in public debt, a drop in oil prices, and the war on terrorism. And the cost of the mass displacement of citizens and the destruction of many infrastructures, and while the revenues decreased, which led to a deficit in the public budget, the state turned to borrowing because the debt was a quick solution to cover this deficit. While the most important recommendations point to the need for the Iraqi government to work on developing a new financial policy in line with the monetary policy, especially in light of the conditions that Iraq is facing from the drop in oil prices, as the goal of this policy is to address the deficit in the public budget, which leads to a lack of continuous need To internal or external borrowing, provided that this does not conflict with the basic functions of the general budget in the field of economic development and achieving economic stability.